Susceptibility of common herbaceous crops to Phytophthora cinnamomi and its influence on Quercus root rot in rangelands - Serrano, María S; Fernández-Rebollo, Pilar; Vita, Paolo; Sánchez, M Esperanza (European Journal of Plant Pathology, 2012)
The susceptibility to Phytophthora cinnamomi of four crops (wheat, oat, vetch, and yellow lupin) commonly planted in rangeland ecosystems in southern Spain was evaluated. By means of in vitro infection experiments, the presence of the pathogen into the roots of yellow lupin (symptomatic) and vetch (asymptomatic) was observed, but never into wheat and oat roots (asymptomatic). It was also demonstrated that yellow lupin stimulated the production of zoospores of P. cinnamomi. Vetch, wheat and oat did not stimulate zoospore production. Under controlled conditions, only yellow lupin induced an increase in the number of viable chlamydospores in the soil. We concluded that the culture of wheat, oat, and vetch in rangelands did not influence the epidemiology of the Quercus root disease, even when asymptomatically-infected vetch is grown, and these crops can constitute an alternative to the culture of yellow lupin in rangeland ecosystems affected by Quercus root rot.
Keywords: Dehesa; Holm oak; oat; vetch; wheat; yellow lupin

Calcium fertilizers induce soil suppressiveness to Phytophthora cinnamomi root rot of Quercus ilex - Serrano, María Socorro; Vita, Paolo; Fernández-Rebollo, Pilar; Sánchez Hernández, María Esperanza (European Journal of Plant Pathology, 2011)
t Based on the observation that the root disease caused by P. cinnamomi on Q. ilex has a low incidence and severity in soils with medium-high Ca 2+ content, we studied the ability of Ca 2+ fertilizers to induce soil suppressiveness to the pathogen. Studies on cultures of P. cinnamomi exposed to different Ca 2+ fertilizers in vitro showed significant inhibition of sporangial, chlamydospore and zoospore production at millimolar concentrations while mycelial growth was mainly unaffected. Experiments performed with artificially infested soil showed that some Ca 2+ fertilizers induce a significant decrease on chlamydospore viability. Additionally, greenhouse experiments using artificially infested soils showed a significant reduction of foliar and root symptom severities in Holm oak seedlings growing in soils amended with Ca 2+ fertilizers. We suggest that limestone amendments in oak rangelands could enhance the suppressiveness of soils to P. cinnamomi, and it is likely that the inhibition of sporangial production was the main mechanism involved.
Keywords: fertilization; limestone; Oak decline; Rangelands

Lupinus luteus, a new host of Phytophthora cinnamomi in Spanish oak-rangeland ecosystems - Serrano, María Socorro; Fernández-Rebollo, Pilar; Vita, Paolo; Carbonero, María Dolores; Trapero, Antonio; Sánchez, María Esperanza (European Journal of Plant Pathology, 2010)
Phytophthora cinnamomi is an aggressive pathogen on Lupinus luteus (yellow lupin), causing root rot, wilting and death of this crop, common in oak-rangeland ecosystems ('dehesas') in south-western Spain. The oomycete, the main cause of Quercus decline in the region, was isolated from roots of wilted lupins in the field. Artificial inoculations on four cultivars of L. luteus reproduced the symptoms of the disease, both in pre- and post-emergence stages, recovering the pathogen from necrotic roots. These results suggest the potential of yellow lupin as inoculum reservoir for the infection of Quercus roots. This is the first report of P. cinnamomi as root pathogen of L. luteus.
Keywords: Oak decline; quercus ilex ssp ballota; Quercus rotundifolia; root rot